Ruling on restricting with the work of the people of Medina and how to submit it on the sources of legislation in the science of assets - NOORALDEEN, FAROOQ ABBAS (Journal of Islamic Sciences, 2019)
After Praise be to Allah, the use of it, I saw that the plan of this research project entitled by virtue of the limitation of the work of the people of medina and how to submit the sources of legislation and its impact on knowledge assets, where there is some controversy when the assets in the rule of jurisprudence and scientists, medina of the Prophet, peace be upon him, the workflow of this controversy, I saw that the work plan of the search above, consists of two sections, the first section consist of two prerequisites, which dealt with the concept of the people of medina (Definition), the rule of restraint in their work, and then listed the various sources of legislation, either on the second section that consist of two prerequisites , the first section examined the causes that lead to a restriction on the sources of legislation, the second section indicated what effects which lead to the restriction of the work of the people of medina in the science of assets, according to the views of the Fundamentalists In conclusion, and then shown The conclusion of research, with the results, with the anniversary of the recommendations research concluded the indexing of the sources and references.